Pre and post-surgical clinical-ultrasound characteristics of children operated on for cryptorchidism at Sabogal Hospital, Perú. - Armas- Alcántara, Luis E. (2022)
Objective: To determine the pre- and post-surgical clinical-ultrasound characteristics of children operated on for cryptorchidism. Material and methods: Descriptive and longitudinal study, data collected from medical records of the Hospital Sabogal, the variables were age at diagnosis, waiting time for orchidopexy, affected testicle, location of the testicle and testicular volume. Results: We included 34 children under 14 years with cryptorchidism, the age of diagnosis was 44 months and orchidopexy 49 months. The waiting time for orchidopexy was 4.72 months, the most affected testicle was the right (58.82%). 39 testicles were included, the primary canalith location (71.79 %), the final scrotal location (50.0%), the operative technique was inguinal (91.18%). The increase in testicular volume was 0.39 cm3, p = 0.0006, 95% CI (-0.62, -0.17). Conclusions: The age of orchidopexy was 49 months and testicular volume increased by 0.39 cm3 after orchidopexy.